Exploring mental health stigma among chinese-english bilinguals: Dual-process model of emotional competence, flipped learning readiness, and academic performance in Mainland Chinese Universities - Pei, Lihua (Frontiers in Psychiatry, 2022)
Due to severe global competition and performance-related academic challenges, Chinese students are compelled to learn English and become bilinguals despite their non-English majors. Consequently, these students frequently experience psychological issues, including mental health stigma. Hence, the present study aims to explore the psychological factors associated with the academic performance of Chinese-English bilinguals as an outcome of their emotional competence, flipped learning readiness, and mental health stigma. Drawing on data from 448 Chinese-English bilingual students in universities in mainland China, the results based on structural equation modeling (SEM) indicated that their academic performance, flipped learning readiness, and emotional competence are negatively influenced by their mental health stigma. Moreover, the findings also validate that both flipped learning readiness and emotional competence significantly mediate the indirect effects of mental health stigma on the academic performance of bilinguals. The study’s implications offer new and compelling evidence on the primary issue of mental health stigma among Gen Z bilingual students to raise deterrence against this psychological menace through collaboration across policymakers, academics, and mental healthcare providers.